Revisiting the 4 R’s: Improving post-release outcomes for rescued mammalian wildlife by fostering behavioral competence during rehabilitation - Goldenberg, Shifra Z.; Parker, Jenna M.; Chege, Stephen M.; Greggor, Alison L.; Hunt, Matt; Lamberski, Nadine; Leigh, Kellie A.; Nollens, Hendrik H.; Ruppert, Kirstie A.; Thouless, Chris; Wittemyer, George; Owen, Megan A. (Frontiers in Conservation Science, 2022)
Rescue, rehabilitation, and release (‘rescue-rehab-release’) of wildlife is an increasingly widespread practice across ecosystems, largely driven by habitat loss, wildlife exploitation and a changing climate. Despite this, its conservation value has not been realized, in part due to the scarcity of what has been termed “the 4th R”, research. Similar to conservation breeding and headstarting, rescue and rehabilitation entails close association of humans and the wildlife in their care over impressionable and extended periods. However, unlike these interventions, rescue and rehabilitation require an initial, and sometimes sustained, focus on crisis management and veterinary needs which can impede the development of natural behaviors and promote habituation to humans, both of which can compromise post-release survival and recruitment. In this perspective, we discuss the pathways toward, and implications of, behavioral incompetence and highlight opportunities for testable interventions to curtail negative outcomes post-release, without compromising the health or welfare of rescued-individuals. We propose that practitioners ‘switch-gears’ from triage to fostering behavioral competence as early in the rehabilitation process as is possible, and that research be implemented in order to develop an evidence-base for best practices that can be shared amongst practitioners. We focus on four mammalian species to illustrate specific contexts and considerations for fostering behavioral competence by building on research in the conservation translocation literature. Finally, we discuss a way forward that calls for greater cross-pollination among translocation scenarios involving extended time under human care during developmentally sensitive periods.